Desenvolvimento de um sistema de monitoramento especializado integrando-o aos processos de gestão de uma empresa de abastecimento público de água visando a redução de perdas do produto - Trojan, Flavio (2006)
This paper has the objective of describing the research, the development and the implementation of a Specialized Monitoring System (SME) integrated to administrative processes, which aims to maintain the water quality and its supply in segments of public basic sanitation systems. Based on levels of product losses, demonstrates the importance of the SME implementation to analyze and prescribe intervention actions in mantenance and orient decisions. It emphasizes the creation of a Specialized Maintenance Management System (GEM), derived from the automated integration between maintenance and the other company departments, such as: the production department, the engineering department and the administrative department. The adopted method is demonstrated in the process studies about Automation and Maintenance Manangement in a basic sanitation company of a city with 300 thousand inhabitants. This method is also demonstrated in the making and the implementation of the SME in this company during 2005/2006. The results obtained in the reduction of water loss, the support in the decision making process and the improving of maintenance management are evident. As conclusion, the paper indicates the SME as an opportunity for improving the control and the management of the maintenance department through its specialized system which integrates and analyses information, reduces the time used in the decision making process as well as prescribes a well-based and consistent way of intervention.